A Comprehensive Study on Maximum Power Point Tracking Techniques Based on Fuzzy Logic Control for Solar Photovoltaic Systems - Zhu, Tongsen; Dong, Jiayi; Li, Xingshuo; Ding, Shuye (Frontiers in Energy Research, 2021)
Maximum power point tracking (MPPT) methods based on fuzzy logic control (FLC) is a popular application in recent years. However, different kinds of fuzzy control methods lack comparative study, which led to confusion in practice. Hence, a comprehensive study on these methods is essential. Unfortunately, very few attempts have been made in this regard. In this paper, four FLC methods are selected for comparative analysis. Futhermore, the design details and experimental result will also be given to help choose and measure these methods, which presents a clear image of the technology of FLC based MPPT to readers.